Innovations in Electronic ID Card Services Through the Digital Residence Identity App in Majalengka Regency - Sherin Amalia Husna Alifa; Iskandar Zulkarnaen (Journal of Comprehensive Science, 2026)
The research problem addressed in this study, titled “Innovations in Electronic ID Card (KTP-el) Services through the Digital Population Identity (IKD) Application in Majalengka Regency,” stems from the public’s lack of interest in switching from the physical KTP-el to the digital ID card, low digital literacy, and the fact that the IKD has not yet been fully integrated into various public service systems which are still used in parallel with the physical KTP-el (dual system). The objective of this study is to analyze the innovation in e-ID card services through the Digital Population Identity (IKD) application in Majalengka Regency, the barriers to its implementation, and the efforts made to improve IKD activation services in Majalengka Regency. The research method employed is qualitative, using a descriptive-analytical approach through in-depth interviews, observations, and document analysis. This study utilized the Diffusion of Innovation theory proposed by Everett M.Rogers, which encompasses the dimensions of innovation, communication channels, time, and social systems. The results indicate that the IKD system offers relative advantages in terms of ease of access and service efficiency; however, its adoption has not yet reached its full potential. Efforts to address this include increasing public awareness, providing direct assistance to the community during the activation process, strengthening the capacity of government officials, improving technical systems, and integrating the IKD into various public services. It is concluded that the IKD innovation has great potential to improve the quality of public services. However, its success is greatly influenced by public acceptance, effective communication, and systemic and policy support.